Första / Sista - Ömalm, Torbjörn (Nordlit, 2020)
Första / Sista are two related catalogue poems in Swedish where listening plays a role as a narrator. The poems aim to paint a picture of current events, places, local history, and self-observation in the urban transitions within the Arctic small towns of Gällivare, Malmberget, and Kiruna. They uncover a repressed sadness when facing the changes that are in motion and the consequences of these. Första is cautiously optimistic while Sista is of a darker, more negative character. The latter also reveals more about the author. The course of events in the poems is not strictly chronological; they are subject-matter scattered with an intention of creating a spontaneous and motley rhythm within the lines. Dialectal words and references to geographic places that carry different names in the local languages ​​Sámi, Meänkieli, and Swedish are key ingredients throughout the text.
Keywords: Katalogdikt; Auto-etnografi; Samhällsomvandling; Sápmi; Dialekt; Samiska; Meänkieli